Why does patients’ discharge delay after vertebral augmentation? A factor analysis of 1,442 patients - Zhao, He; Zhang, Zhengping; Wang, Yanjun; Qian, Bing; Cao, Xinhao; Yang, Ming; Liu, Yangjin; Zhao, Qinpeng (Frontiers in Surgery, 2022)
Objective: Vertebral augmentation techniques are widely used to treat osteoporotic vertebral compression fractures (OVCFs). Superior analgesic effects and shortened bed rest time make patients recover quickly, but unscheduled prolonged hospitalization can increase medical expenses and the risk of bed rest complications. The aim of this study was to investigate the reasons for prolonged hospitalization after vertebral augmentation surgery and to determine the relative risk factors. Methods: A single-center retrospective study was conducted to enroll patients with OVCFs and accepted vertebral augmentation surgery from January 2017 to December 2017. Clinical information was collected from the Hospital Information System (HIS). The criteria of delayed discharge was postoperative hospitalization >3 days. Telephone interviews and medical history evaluations were carried out to confirm the exact reason for retention. The risk factors were analyzed by multiple logistic regression. Results: Overall, 1442 patients were included, 191 (13.2%) stayed in the hospital for more than 3 days postoperative. The reasons for delayed discharge were psychological factors (37.2%), residual pain (32.5%), cardiopulmonary complications (15.7%), nonspecific symptoms (8.4%), incision abnormalities (2.6%), thrombosis (2.1%) and post-anesthesia reactions (1.6%). The multiple logistic model was significant, Age (OR 1.028; 95% CI 1.009-1.046), pre-operative stay (OR 1.192; 95% CI 1.095-1.298), operation type (OR 1.494; 95% CI 1.019-2.189) and number of surgical segments (OR 2.238; 95% CI 1.512-3.312) showed statistical significance. In contrast, gender (P >0.1) and chronic comorbidities (P >0.1) were not predictors in this model. Conclusion: Overall, 13.2% of OVCF patients underwent vertebral augmentation surgery were not discharged within 3 days postoperatively and several predictors were found out. Preoperative communication and comprehensive evaluations are calling for more attention, physicians should adopt an appropriate medical process to enhance rehabilitation in geriatric orthopedics.